Telephone-based Support in Preventing Stoma and Peristomal Complications: A Review of Literature - Rose A Nain; Fatimah Ahmedy; Deena Clare Thomas (Scientific Foundation SPIROSKI, Skopje, Republic of Macedonia, 2022)
A stoma is classified as either permanent or temporary depending on the time of anastomosis, and is referred to as a colostomy, ileostomy, or urostomy based on the organ to which it is anastomosed. The creation of a stoma poses many challenges to patients as they adapt to this profound life-changing event that affects fundamental aspects of quality of life. To reduce the risk of stoma and peristomal complications after discharge, telephone-based support (TBS) program which includes patient follow-up, counselling, and the benefits of group support activities including information sharing, health education and counselling, symptom management, early detection of problems, reassurance, and high-quality aftercare. This article narrates common stoma and peristomal complications as well as TBS program to support in reducing these complications.